Analisis Kebutuhan SDM Rekam Medis Sebelum dan Sesudah Implementasi RME dengan Metode ABK-Kes - Selvi Dwi Lestari; Laela Indawati; Daniel Happy Putra; Deasy Rosmala Dewi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Healthcare human resource planning is crucial for determining current and future staffing needs and availability. Therefore, healthcare workload analysis is essential in the healthcare sector for evaluating healthcare human resources. The objective of this study is to determine the staffing needs for medical record technicians and health information officers at a hospital in East Jakarta. This study is a quantitative descriptive study conducted through direct field research to determine the required number of medical records staff based on data from interviews and observations. The results of this study indicate that the Available Work Time (AWT) is 1,200 hours/year or 72,000 minutes/year. The Support Task Factor (STF) is 14% and the Support Task Standard (STS) is 1.16, resulting in a requirement for 15 medical records staff. There are currently 10 medical records staff members, so an additional 5 staff members are needed to meet staffing requirements. However, if a hospital in East Jakarta were to fully implement Electronic Medical Records (EMR), the staffing requirement would be reduced to 6 staff members, resulting in a surplus of 4 staff members since some tasks would be performed electronically via the system. The recommendation for the hospital is to accelerate the full implementation of Electronic Medical Records (EMR) to improve work efficiency and reduce the workload in certain departments. Staff who do not yet meet the qualifications are advised to pursue education in medical records and receive training to enhance their knowledge and skills in line with advancements in technology and modern healthcare systems.